2023
DOI: 10.3389/frobt.2022.813907
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic human-robot collaboration in industry: A review

Abstract: In the current industrial context, the importance of assessing and improving workers’ health conditions is widely recognised. Both physical and psycho-social factors contribute to jeopardising the underlying comfort and well-being, boosting the occurrence of diseases and injuries, and affecting their quality of life. Human-robot interaction and collaboration frameworks stand out among the possible solutions to prevent and mitigate workplace risk factors. The increasingly advanced control strategies and plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 239 publications
0
21
0
Order By: Relevance
“…Currently, workers are assessed using wearable, wireless, and miniaturized technology while doing manual material handling tasks ( 15 , 16 , 23 , 24 ). Bipolar and high-density surface electromyography are used to estimate muscle behavior, insoles and sensorized shoes are used to measure reaction forces (kinetics), and inertial measurement units (IMUs) and 3D depth cameras are utilized for whole-body 3D reconstructions (kinematics) ( 15 , 16 , 23 ).…”
Section: Identifying the Most Appropriate Technologies For Movement M...mentioning
confidence: 99%
“…Currently, workers are assessed using wearable, wireless, and miniaturized technology while doing manual material handling tasks ( 15 , 16 , 23 , 24 ). Bipolar and high-density surface electromyography are used to estimate muscle behavior, insoles and sensorized shoes are used to measure reaction forces (kinetics), and inertial measurement units (IMUs) and 3D depth cameras are utilized for whole-body 3D reconstructions (kinematics) ( 15 , 16 , 23 ).…”
Section: Identifying the Most Appropriate Technologies For Movement M...mentioning
confidence: 99%
“…Additionally, they concluded that the interaction can affect stress and mental workload either positively or negatively. Lorenzini et al [18] conducted a narrative review to identify the most effective assessment methods for physical and cognitive ergonomics in workplace environments. Their review focused on available monitoring technologies that endow robots with the ability to adapt online to the mental states and physical needs of workers.…”
Section: Related Workmentioning
confidence: 99%
“…This highlights the importance of defining and classifying human factors in a more precise and standardized way to avoid unintentional research bias. To address this challenge, we explored various classification schemes, such as dividing the human factors into cognitive and physical ergonomics, as proposed by Lorenzini [18], or further categorizing them into load and perceptual factors. However, we found that the human factors in pHRI, which involved both domestic and industrial scenarios, are more complex and diverse than these schemes can account for, as they may involve emotional factors in addition to cognitive and physical ones.…”
Section: Literature Gapmentioning
confidence: 99%
“…Researchers in the HRI domains have long focused on understanding human physical and cognitive dynamics as they relate to safety and performance in a collaborative setting Lorenzini et al (2023). In scenarios where humans are assigned the role of teacher to a cyber-physical student, the added responsibility of the learner's performance places a greater burden on their shoulders.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring Human Teaching Role. In the field of human-robot interaction (HRI), several efforts Lorenzini et al (2023) to model and assess human behavior in collaboration or interaction with robots. However, in teaching new skills through PbD, the emphasis is persistently placed on the robot's performance.…”
Section: Introductionmentioning
confidence: 99%